2004
DOI: 10.1016/j.cardiores.2003.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Connexins in leukocytes: shuttling messages?

Abstract: Gap junctions, formed by the connexin (Cx) protein family, are intercellular channels that permit the cytoplasmic exchange of ions and small metabolites between neighboring cells, a process called gap junction intercellular communication (GJIC). These channels possess unique properties, including distinctive permeabilities for various signaling molecules, which depend on the connexin member(s) that form them. Importantly, GJIC must be properly controlled as its misregulation might contribute to diseases. Morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 78 publications
3
37
0
Order By: Relevance
“…Connexins may regulate leukocyte trafficking into inflamed tissues. 131 Connexins form gap junctions that connect adjacent cells and permit intercellular communication. 132 Gap junctions may form between leukocytes and leukocytes, or leukocytes and endothelial cells.…”
Section: Connexinsmentioning
confidence: 99%
“…Connexins may regulate leukocyte trafficking into inflamed tissues. 131 Connexins form gap junctions that connect adjacent cells and permit intercellular communication. 132 Gap junctions may form between leukocytes and leukocytes, or leukocytes and endothelial cells.…”
Section: Connexinsmentioning
confidence: 99%
“…This process, termed gap junction-mediated intercellular communication (GJIC), is a widespread mechanism for the maintenance of homeostasis in tissues and organs. In the immune system, the existence and physiological role of GJIC between several types of immune cells have been reported (12,13). Indeed, many immune cells (e.g., T cells, B cells, macrophages, mast cells, and follicular DCs) have been found to form homotypic interactions with themselves or heterotypic interactions with other cell types via gap junctions (12,13).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…Indeed, many immune cells (e.g., T cells, B cells, macrophages, mast cells, and follicular DCs) have been found to form homotypic interactions with themselves or heterotypic interactions with other cell types via gap junctions (12,13). With respect to functional aspects of GJIC, it is considered to be involved in hematopoiesis (14), T cell development in the thymus (15), inflammation (13), transendothelial migration of macrophages (16) and neutrophils (17), and Ab formation in the germinal center (18,19). Very recently, Neijssen et al (20) have revealed a novel mechanism of cross-presentation via GJIC.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, inhibition of gap junctions increases neutrophil but decreases monocyte migration (Wong et al 2004). The inhibitory effect of gap junction expression on PMN migration appears to involve heterotypic (i.e.…”
Section: Sex Differences In Leukocyte Recruitmentmentioning
confidence: 99%